Fulfillment of Human Rights By Transnational Corporations In Indonesia: Perspective of International Norms - Brigitta Raras Ayu Roesedi; Arina Bhuana Sari; Isnin Harianti; Gisca Azaria Ramadhani (Faculty of Law, Merdeka University Surabaya, Indonesia, 2022)
Leniency in the implementation of rules on the fulfillment of human rights by the Government to TNC as an entity in Indonesia. This research aims to describe the fulfillment of human rights by transnational corporations inÂ International Norms. This research used normative research methods, focusing on the differences that occur in the field (das sein) namely the policy of the Government of Indonesia in realizing the fulfillment of human rights by TNC, with legal norms that should be implemented (das sollen) namely international norms. The data source used is a primary and secondary data source with a deductive thinkingpattern. The results showed thatÂ the State as a duty holder for citizens, is authorized to issue regulations on human rights respect by TNC in order to minimize human rights violations. Domestic regulations are necessary to be the attachment of TNC operating within the territory of the country to be subject to the applicable constitutional rules, so that respect, protection, and rehabilitation of human rights can run optimally.